ANALISIS KEPUTUSAN PEMBELIAN : FENOMENA MASKER DAN VITAMIN DI MASA PANDEMI - Rizka Ambar Sari; Ari Susanti (Journal of Management Small and Medium Enterprises (SMEs), 2022)
The occurrence of the COVID-19 pandemic caused significant changes to the operation of a company. In addition, with government regulations to carry out activities inside the house and limit contact with the outside environment, it causes panic buying by the public. this is an attraction for business actors in seeing business opportunities selling vitamin and mask products. This study focuses on the analysis of purchasing decisions for masks and vitamins by paying attention to the current phenomena, namely the importance of price, panic buying and service convenience that affect purchasing decisions. The population in this study was 150 responses from PT Sanbe Farma employees who were carried out by filling out online questionnaires via google form. Furthermore, statistical tests were carried out to determine the relationship between prices, the emergence of panic buying attitudes and service convenience during the pandemic. The results showed that there was a significant relationship between panic buying, price and service convenience on purchasing decisions. on the second variable test , the price has a significant effect on purchasing decisions . in this case the employees of PT. sanbe Farma group still considers the affordability of prices, the purchasing power of employees for the products to be purchased and considers the quality of the goods to be obtained as important factors in shopping. while for the third variable, service convenience is significantly influenced by ease of accessing applications, ease of transaction and convenience in shopping due to social distancing. Keywords: Panic Buying, Price, Service Convenience, Purchase Decision